Total Polyphenol Content of Bromelia Leaves (Neoregelia marmorata) Etanol Extract : Kandungan Polifenol Total Ekstrak Etanol Daun Bromelia (Neoregelia marmorata) - Safitri, Malikah; Susanti, Erna (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine total polyphenol content of Bromelia (Neoregelia marmorata) leaves extract with ethanol and water solvent ratio. There are three kinds of comparisons, ethanol 96%, ethanol 50 % and aquadest. The third variation of the extract is then determined the total polyphenol content. Determination of total polyphenol content was performed using visible light spectrophotometry at wavelength 758 nm with Folin-ciocalteu reagent and standard used was gallic acid. The highest average polyphenol content was obtained ethanol extract 96% then ethanol 50%, aquadest that is 0,4710 mgGAE / g; 0.3677 mgGAE / g; 0.1847 mgGAE / g. The more part of ethanol 96%, the total polyphenol content is higher. Furthermore, one way anova test is used to know the difference in the three extracts and followed by Post Hoc test. The results of the analysis showed significant differences between the three variants extract with probability value (p≤0,05).